Reação de β-dimetilaminovinil cetonas com hidroxilamina: regioquímica de formação de 4,5-diidroisoxazóis e de isoxazóis - Rosa, Fernanda Andreia (2005)
The regiochemistry study of the formation of a series of aryl-, heteraryl- and haloalkyl-substituted isoxazoles from the reaction of β-dimethylaminovinyl ketones and hydroxylamine is reported. The precursors β-imethylaminovinyl ketones were obtained from the condensation reaction of N,N-dimethylformamide dimethyl acetal and the substituted ketones [R-C(O)-CH3, where R = Ph, MeO-4-C6H4, Me-4-C6H4, F-4-C6H4, Cl- 4-C6H4, Br-4-C6H4, O2N-4-C6H4, Fur-2-yl, Tien-2-yl, Pyrrol-2-yl, Pyrid-2-yl, and CCl3]. The study shown that for R = trichloromethyl substituent was obtained regiospecifically 5-halomethyl-4,5-dihydroisoxazoles. For precursors with R = O2N-4-C6H4, Fur-2-yl were obtained 3-aryl-4,5-dihydroisoxazole, for R = MeO-4-C6H4, F-4-C6H4, Br-4-C6H4, Pyrrol-2-yl were obtained 5-aryl[heteroaryl]isoxazoles, and for remainder substituents (R = Ph, Me-4-C6H4, Cl-4-C6H4, Tien-2-yl, Pyrid-2-yl) were obtained a mixture of the 4,5-dihydroisoxazoles-1,3 and isoxazoles-1,5. The effect of the substituent on the regiochemistry of isoxazoles obtained was discussed with bases on a MO calculations data.